1997
DOI: 10.1080/016502597385388
|View full text |Cite
|
Sign up to set email alerts
|

Microgenetic Change in the Quantity and Quality of Preschoolers’ Private Speech

Abstract: Forty preschool-aged children were videotaped while carrying out paperfolding and story-sequencing tasks, during a series of three experimenta l sessions. During the rst session, participants worked on both easy and dif cult items, and in the second and third sessions they worked on familiar items (the rst session dif cult items, presented repeatedly) and novel items, of each task type. Participants used more private speech on dif cult/novel items than on easy/familiar items, during all three sessions. Private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 10 publications
2
38
0
1
Order By: Relevance
“…The main prediction of Vygotesky is that private speech increases with increased difficulty of task. This prediction was supported in studies on children (Beaudichon, 1973;Duncan and Pratt, 1997;KohLberg et al, 1968) and young adults (Duncan and Cheyne, 2002). Berk and Garvin (1984) deeply investigated Vygotesky's theory.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The main prediction of Vygotesky is that private speech increases with increased difficulty of task. This prediction was supported in studies on children (Beaudichon, 1973;Duncan and Pratt, 1997;KohLberg et al, 1968) and young adults (Duncan and Cheyne, 2002). Berk and Garvin (1984) deeply investigated Vygotesky's theory.…”
supporting
confidence: 54%
“…Berk (1986) observed that first and second grade students use private speech to guide their thoughts during solving difficult math problems. 4 -6 years old subjects of Duncan and Pratt (1997) used private speech to designwriting tasks and chain story plans. Matuga (2003Matuga ( /2004 observed first, third and fifth grade subjects used private speech to design strategies before working on tasks.…”
mentioning
confidence: 99%
“…Vygotsky's original (1934Vygotsky's original ( /1987 prediction that private speech will increase linearly with task difficulty has been supported both in studies of children (Beaudichon, 1973;Duncan & Pratt, 1997;Kohlberg et al, 1968) and young adults (Duncan & Cheyne, 2002).…”
Section: Private Speech and Task Difficultymentioning
confidence: 91%
“…A variety of different aspects of children's private speech have now been explored, including ontogentic and microgenetic developmental trajectories (Berk, 1986;Berk & Spuhl, 1995;Duncan & Pratt, 1997;Winsler, Diaz, Atencio, McCarthy, & Adams Chabay, 2000), links with adult-child interactions (Berk & Spuhl, 1995;Winsler, Diaz, McCarthy, Atencio, & Adams Chabay, 1999), task and situational influences (Frauenglass & Diaz, 1985;Krafft & Berk, 1998;Winsler, Carlton, & Barry, 2000;Winsler & Diaz, 1995), children's awareness of such speech (Manfra & Winsler, in press;Winsler & Naglieri, 2003), and private speech use within special populations of children (Berk & Landau, 1993;Berk & Potts, 1991;Winsler, 1998). However, an early and central theme of inquiry in this area has been determining the extent to which private speech is helpful to children in terms of either guiding motor behavior or enhancing task performance (Fernyhough & Fradley, 2005).…”
Section: Research On Private Speechmentioning
confidence: 99%